Middle Ordovician Drepanoistodus (Vertebrata, Conodonta) from Baltica, with description of three new species - Rasmussen, Jan Audun; Eriksson, Mats E.; Lindskog, Anders (European Journal of Taxonomy, 2021)
Drepanoistodus basiovalis (Sergeeva, 1963) is a common conodont species in Middle Ordovician strata of Baltica. For many years it has been widely accepted that the species encompasses a wide range of morphological plasticity. Hence, several different morphotypes that significantly deviate from the holotype have nonetheless been included in the broad species concept. In this study, we performed a detailed taxonomical study on 112 predominantly well-preserved specimens (geniculate elements) from the St. Petersburg region of Russia; 37 of these were selected for morphometric analyses together with 21 well-illustrated specimens from the published literature. The results demonstrate that, among the morphotypes that share some characteristics with D. basiovalis sensu lato, at least five species can be readily distinguished. Hence, three new species – Drepanoistodus iommii sp. nov., D. svendi sp. nov. and D. viirae sp. nov. – are here added to the previously known D. basiovalis and D. contractus (Lindström, 1955). In addition, some specimens were left under open nomenclature and assigned to Drepanoistodus aff. basiovalis and D. cf. suberectus (Branson & Mehl, 1933). In order to objectively compare the Drepanoistodus taxa and test the validity of the new species, we performed a Principal Component Analysis combined with non-parametric (PERMANOVA) tests based on 21 morphological characters.